2011
DOI: 10.1186/1741-7015-9-125
|View full text |Cite
|
Sign up to set email alerts
|

Regular consumption of vitamin D-fortified yogurt drink (Doogh) improved endothelial biomarkers in subjects with type 2 diabetes: a randomized double-blind clinical trial

Abstract: BackgroundEndothelial dysfunction has been proposed as the underlying cause of diabetic angiopathy that eventually leads to cardiovascular disease, the major cause of death in diabetes. We recently demonstrated the ameliorating effect of regular vitamin D intake on the glycemic status of patients with type 2 diabetes (T2D). In this study, the effects of improvement of vitamin D status on glycemic status, lipid profile and endothelial biomarkers in T2D subjects were investigated.MethodsSubjects with T2D were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
137
2
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(150 citation statements)
references
References 43 publications
6
137
2
5
Order By: Relevance
“…Of the 23 studies that were included in the systematic review, 13 reported fasting glucose as primary or secondary outcome measure (19,20,21,22,23,24,26,27,28,32,35,36,39). Three studies reported a significant reduction in fasting glucose level after vitamin D supplementation (21,28,39).…”
Section: The Effect On Fasting Glucosementioning
confidence: 99%
See 3 more Smart Citations
“…Of the 23 studies that were included in the systematic review, 13 reported fasting glucose as primary or secondary outcome measure (19,20,21,22,23,24,26,27,28,32,35,36,39). Three studies reported a significant reduction in fasting glucose level after vitamin D supplementation (21,28,39).…”
Section: The Effect On Fasting Glucosementioning
confidence: 99%
“…The quality assessment of the studies resulted in 14 out of 23 studies having a good quality (Appendix 1, see section on Appendix given at the end of this article) (12,19,20,21,22,23,24,25,26,27,28,29,30,31). The main characteristics and main outcomes of the included studies are given in Table 1.…”
Section: Description Of the Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The study of Wasse et al (13) reported the finding of a significant inverse correlation between 25(OH)D concentration and MMP-9 concentration in patients with terminal renal failure. Another study by Shab-Bidar et al (15) reported that regular consumption of vitamin D-fortified yogurt drink (doogh) for 12 weeks resulted in a significant improvement in endothelin-1, endothelial selectin and MMP-9 in subjects with type 2 diabetes. The study of Baker et al (16) showed a significant inverse correlation between MMP-9 and vitamin D levels (r=-0.41; p=0.01).…”
Section: Introductionmentioning
confidence: 99%